2021
DOI: 10.1038/s41598-021-84271-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlling wave fronts with tunable disordered non-Hermitian multilayers

Abstract: Unique and flexible properties of non-Hermitian photonic systems attract ever-increasing attention via delivering a whole bunch of novel optical effects and allowing for efficient tuning light-matter interactions on nano- and microscales. Together with an increasing demand for the fast and spatially compact methods of light governing, this peculiar approach paves a broad avenue to novel optical applications. Here, unifying the approaches of disordered metamaterials and non-Hermitian photonics, we propose a con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Moreover, we have found that the real-complex transition also demonstrates cascade behavior, similar to the delocalization transition for the excited states. Besides the non-reciprocal hopping, the non-Hermiticity can also be induced by the on-site gain/loss [28,36,[71][72][73]. It should be interesting to study the delocalization transition and the critical behavior in the IAAF model with on-site gain/loss.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have found that the real-complex transition also demonstrates cascade behavior, similar to the delocalization transition for the excited states. Besides the non-reciprocal hopping, the non-Hermiticity can also be induced by the on-site gain/loss [28,36,[71][72][73]. It should be interesting to study the delocalization transition and the critical behavior in the IAAF model with on-site gain/loss.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the incoherent waveforms with longer characteristic timescales such as incoherent solitons [57] and optical kinks [58,59] can also withstand absorption in resonant media. We also mention the studies of ultrashort pulses [60] and wavefront propagation [61] in disordered resonantly absorbing and amplifying media. The role of driving-field decay rate in superradiance and subradiance dynamics was revealed recently [62].…”
Section: Ones)mentioning
confidence: 99%
“…The most popular transverse geometry is a multilayer structure with alternating loss and gain media. Being a non-Hermitian generalization of the photonic crystal concept, such a multilayer attracts much attention due to its simplicity for analysis and availability for unusual optical responses, such as anisotropic transmission resonances, resonant scattering, nonlinear saturation effects, nonlocality, pulse-propagation effects, , effects of disorder, and so forth. From the more general perspective, many of these effects can be treated as “anomalies” in light scattering , being described by means of scattering matrix technique. , The features of light scattering on dielectric structures were deeply studied in recent years. …”
Section: Introductionmentioning
confidence: 99%